2018
DOI: 10.1364/ol.43.002795
|View full text |Cite
|
Sign up to set email alerts
|

Fibonacci terahertz imaging by silicon diffractive optics

Abstract: Fibonacci or bifocal terahertz (THz) imaging is demonstrated experimentally employing a silicon diffractive zone plate in continuous wave mode. Images simultaneously recorded in two different planes are exhibited at 0.6 THz frequency with the spatial resolution of wavelength. Multifocus imaging operation of the Fibonacci lens is compared with a performance of the conventional silicon phase zone plate. Spatial profiles and focal depth features are discussed varying the frequency from 0.3 to 0.6 THz. Good agreem… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…To reduce the losses, high-density polyethylene (HDPE) materials or polyamide layers can be replace by high-resistivity silicon-based multilevel phase Fresnel lenses [211] or zone plates (Figure 4) fabricated, for instance, by laser ablation technology [212]. It was shown that such components can successfully be used for THz beam focusing, as well as beam-engineering, for instance, in Bessel or Fibonacci-beam generation [213,214]. The approach works well even for large apertures, up to 50 mm [215], and it allows for reaching nearly 90% transmittance of silicon antireflection layers and produce focusing by binary zone plates [216].…”
Section: Diffractive Optical Components and Beamforming (Beam Engineering) In Thz Imagingmentioning
confidence: 99%
“…To reduce the losses, high-density polyethylene (HDPE) materials or polyamide layers can be replace by high-resistivity silicon-based multilevel phase Fresnel lenses [211] or zone plates (Figure 4) fabricated, for instance, by laser ablation technology [212]. It was shown that such components can successfully be used for THz beam focusing, as well as beam-engineering, for instance, in Bessel or Fibonacci-beam generation [213,214]. The approach works well even for large apertures, up to 50 mm [215], and it allows for reaching nearly 90% transmittance of silicon antireflection layers and produce focusing by binary zone plates [216].…”
Section: Diffractive Optical Components and Beamforming (Beam Engineering) In Thz Imagingmentioning
confidence: 99%
“…Focusing of the radiation does not have to be limited to a single focal spot but can also be understood as forming multiple focal spots (one after another), creating focal curves of different shapes or functioning for a broader range of frequencies. The Fibonacci lens design [79,80] was used to form bifocal diffractive lenses realized as binary structures with zone widths and position calculated according to the golden ratio [81]. Such elements were used to point-to-point imaging of volume objects-two planes corresponding to two focal lengths were imaged simultaneously forming an image with wavelength resolution.…”
Section: Efficient Focusing Of Thz Radiationmentioning
confidence: 99%
“…To obtain better performance of focusing, the typical design of the Fresnel zone plate can be substituted by fractal and Fibonacci lens-like structures [94]. The Fibonacci structure has been used for bifocal imaging which enables obtaining better resolution [95]. Additionally, DOEs can focus the incident wavefront into different shapes of focal curves [96,97]-like segments shorter and longer than the size of the structure, rings, lines, and matrix of points [98,99].…”
Section: Advanced Diffractive Optical Elementsmentioning
confidence: 99%